Citizen Brown: race, democracy, and inequality in the St. Louis suburbs - Gordon, Colin (University of Chicago Press, 2020)
Introduction -- Fragmenting citizenship: municipal incorporation and annexation -- Segregating citizenship: schools, safety, and sewers -- Bulldozing citizenship: renewal, redevelopment, and relocation -- Arresting citizenship: segregation, austerity, and predatory policing -- Conclusion.